2003
DOI: 10.1016/s1074-7613(02)00513-7
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for the Selection of Dominant αβ T Cell Receptors in Antiviral Immunity

Abstract: We have examined the basis for immunodominant or "public" TCR usage in an antiviral CTL response. Residues encoded by each of the highly selected genetic elements of an immunodominant clonotype recognizing Epstein-Barr virus were critical to the antigen specificity of the receptor. Upon recognizing antigen, the immunodominant TCR undergoes extensive conformational changes in the complementarity determining regions (CDRs), including the disruption of the canonical structures of the germline-encoded CDR1alpha an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
324
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 318 publications
(345 citation statements)
references
References 53 publications
15
324
0
Order By: Relevance
“…Previous studies with TCR Tg T cells indicate that such selection reflects differing TCR avidity profiles (37,43). As such, enrichment of TRBV bias from the naive into the immune repertoire is presumably due to the preferential selection/proliferation of CTLps with "optimal-fit" TCRs (37,43,44).…”
Section: Figurementioning
confidence: 99%
“…Previous studies with TCR Tg T cells indicate that such selection reflects differing TCR avidity profiles (37,43). As such, enrichment of TRBV bias from the naive into the immune repertoire is presumably due to the preferential selection/proliferation of CTLps with "optimal-fit" TCRs (37,43,44).…”
Section: Figurementioning
confidence: 99%
“…Structural analysis of TCRs binding related APLs did not reveal any significant differences in the TCR-pMHC interaction to explain agonist vs antagonist activation (3), but a recent study has identified a conformational change in TCR␣ structure during TCR-pMHC binding (4). This remains to be confirmed in other structures.…”
mentioning
confidence: 90%
“…Despite this vast potential repertoire, immune responses often show strong bias in TCR selection, resulting in immunodominance of certain "public" TCRs that are widely used in individuals with shared MHC types (2)(3)(4)(5). Structural studies have shown that biased TCR usage arises from unique specificity requirements for a given peptide-MHC complex (6,7). Furthermore, TCR production frequency during recombination in the thymus also contributes to bias in TCR usage in Ag-specific responses, with public TCRs generally produced with fewer random nucleotide additions in their sequence (8).…”
mentioning
confidence: 99%